PENGEMBANGAN E-MODUL MATA KULIAH STRATEGI PEMBELAJARAN - Nyoman Sugihartini; Nyoman Laba Jayanta (Jurnal Pendidikan Teknologi dan Kejuruan, 2017)
This study aimed to develop and produce a product of e-module learning media in the subject of CAI-based Learning Strategy with project based learning, in order to improve the mastery of student concepts and graduate competencies, especially in the mastery of the concept of Pedagogic as a prospective teacher. To produce the expected product, the method to be used in the achievement of the goal is the development method using the ADDIE model consisting of five stages: 1) analysis, 2) design, 3) development, 4) implementation and 5) evaluation. In the analysis phase, analyzes are related to system requirements and instructional goals  learning strategy subject to syllabus / SAP. At the design stage is done systematic design of learning strategy module with project based learning as well as done stages of system design, database, and interface. Development stage is a continuation of what has been designed, ie compiling the module content in accordance with the syllabus / SAP with project based learning and create a system based on CAI, in this case LMS (Learning Management System) used is Moodle. Implementation stage is to insert the module content into Moodle, in other words, Moodle as a container of learning strategy module, so as to produce e-Module.Keywords: e-Modul, Moodle, CAI, Project Based learning